The auditor’s dependence on internal control in evaluating computerized systems : Exploratory research of the views of a sample of employees in banks operating in the Kurdistan region/ Iraq - Miran Omer Amin; Rizgar Ali Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This research aims to explore the dependence of auditors on internal control when evaluating computerized systems in the Kurdish Region of Iraq. To achieve the research objectives and address the research questions, a questionnaire was utilized as the research instrument. The questionnaire was distributed among two groups of samples, which encompassed the relevant employees in active banks within the Kurdish Region of Iraq. Four banks and their branches were selected for the study, with a total of 95 questionnaires distributed as the research sample; 83 of these questionnaires were returned and included in the analysis. The questionnaire data were collected and analyzed using the Statistical Package for the Social Sciences (SPSS) and Microsoft Excel. The research yielded several conclusions, notably demonstrating a positive correlation between the auditor’s role and the evaluation of computerized systems. This correlation was observed through flowchart analysis and the design and validation of the system. The auditor's involvement was found to have a positive impact on the evaluation and auditing of computerized systems and their performance in the active banks of the Kurdistan Region of Iraq. The researcher recommends that banks in the Kurdistan Region of Iraq prioritize keeping pace with rapid technological advancements in the modern and fiercely competitive environment. This involves offering products that efficiently cater to customer needs, ensuring speed, accuracy, and high quality